Hubungan Ekspresi Reseptor Progesteron dan Ki-67 Labeling Index dengan Derajat Histopatologik Meningioma - Dwi Sri Rejeki; Salmiah Agus; Yuliarni Syafrita (Majalah Patologi Indonesia, 2019)
BackgroundMeningioma is tumor originating from meningothelial cells (arachnoid) attached to duramater. These is thesecond most tumor in central nervous system. All degrees meningioma have risk for recurrence, unfortunatelythe biologic behavior of meningioma can’t be seen from histopathology alone. Therefore, many studies haveshown progesterone receptor influence the degree of meningioma and Ki-67 LI also has important role indetermining risk of recurrence in the degree meningioma. Therefore, the examination of progesterone receptorand Ki-67 LI in meningioma is required to see character of meningioma tumor cells and hence to determinetreatment and prognosis.MethodsThe study was a cross-sectional study, which conducted patients with diagnosis of meningioma from 5Pathological Anatomy Laboratories in West Sumatra. Total of 64 cases meningioma were obtained duringJanuary 2012 to December 2015 and 35 samples were taken and met the inclusion criteria.Immunohistochemical examination was using specific antibodies to progesterone receptor and Ki-67. Datacollected were analyzed using the Kruskal-Wallis test and p value <0.05 was considered as statisticallysignificant.ResultsFrom 35 samples, 29 samples (82.9%) classified meningioma grade I, 4 samples (11.4%) meningioma grade IIand 2 samples (5.7%) meningioma grade III. Meningioma was most prevalent the age range 41-50 years,female gender and histopathological grade I.ConclusionNo differences expression progesterone receptor on the degree histopathological meningioma. No differencesexpression Ki-67 LI on the degree histopathological meningioma. There is inverse relationship betweenexpression progesterone receptor and Ki-67 LI on the degree histopathological meningioma